2019
DOI: 10.1021/acs.est.9b02448
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro, in Vivo, and Spectroscopic Assessment of Lead Exposure Reduction via Ingestion and Inhalation Pathways Using Phosphate and Iron Amendments

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…Phosphate-modified biochar and biochar produced from feedstocks that are rich in P such as animal carcass may remarkably reduce Cd and Pb bioavailability or bioaccessibility by forming stable precipitates [e.g., Cd 3 (PO 4 ) 2 , Cd 5 (PO 4 ) 3 Cl; Pb 5 (PO 4 ) 3 Cl, Pb 5 (PO 4 ) 3 OH, Pb 3 (PO 4 ) 2 ] (Chen et al 2019b;Deng et al 2019c;Penido et al 2019). Kastury et al (2019) also found that phosphaterich biochar (bone meal biochar) was effective in reducing the exposure risk of Pb to mice, which provides an effective remediation strategy to mitigate the exposure risk of heavy metals to animals (Kastury et al 2019). Iron (Fe) oxidesloaded biochars are still widely used in heavy metal remediation in 2019.…”
Section: Heavy Metal Immobilizationmentioning
confidence: 99%
“…Phosphate-modified biochar and biochar produced from feedstocks that are rich in P such as animal carcass may remarkably reduce Cd and Pb bioavailability or bioaccessibility by forming stable precipitates [e.g., Cd 3 (PO 4 ) 2 , Cd 5 (PO 4 ) 3 Cl; Pb 5 (PO 4 ) 3 Cl, Pb 5 (PO 4 ) 3 OH, Pb 3 (PO 4 ) 2 ] (Chen et al 2019b;Deng et al 2019c;Penido et al 2019). Kastury et al (2019) also found that phosphaterich biochar (bone meal biochar) was effective in reducing the exposure risk of Pb to mice, which provides an effective remediation strategy to mitigate the exposure risk of heavy metals to animals (Kastury et al 2019). Iron (Fe) oxidesloaded biochars are still widely used in heavy metal remediation in 2019.…”
Section: Heavy Metal Immobilizationmentioning
confidence: 99%
“…Pb exposure can affect human health in various ways such as neurological disorders in children, malfunction of kidneys, cardiovascular problems, genotoxicity, and disruption of stress mechanisms which can cause neurotoxicity [ 56 , 57 ]. Incidental ingestion and inhalation of soil/dust particles are considered major sources of Pb exposure in human beings [ 57 ]. The heavy concentration of Pb in road dust samples of both cities indicates traffic as a major source of pollution.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were digested using a block digester (A.I. Scientific AIM500) by slowly ramping up the temperature to a maximum of 170 °C until the organs were dissolved and the samples dried to near evaporation (~ 1-2 mL) 55 . The samples were made up to 10 mL using MilliQ water, vortexed thoroughly to mix, syringe filtered (0.45 µm) to separate the dissolved metal(loid)s and stored at 4 °C Figure 1.…”
Section: Necropsy Carcasses Were Necropsied According To Well-establmentioning
confidence: 99%